Strategi Pengembangan Perikanan Tangkap di Kabupaten Bangka Selatan - Kurniawan Kurniawan (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2018)
Capture fishery in South Bangka Regency has the prospect to be developed as one of the leading sectors in regional economic development. The purpose of this research is to know and provide fish resource development plan in South Bangka Regency. The method used is descriptive method, with the taking of survey data, survey and study of relevant literature. SWOT analysis was conducted to make capture fisheries development strategy in South Bangka Regency. The results showed that South Bangka Regency has potential of fishery potential. While capture fisheries development strategy in South Bangka Regency are social, economic and sustainable development strategy, human resources strategy and development, promotion strategy for potential resources for development and development of facilities and infrastructure. supporters of fisheries development.